EFFECT OF SERVICE QUALITY MANAGEMENT ON STUDENT SATISFACTION - Nuning Nurna Dewi (STKIP Singkawang, 2021)
This study aims to determine whether empathic services, facility services, reliable services, responsive services and convincing services have an effect on student satisfaction. The research method used is to take a sample from a population and use a questionnaire as the main data collection. To dig up information / data and distribute it to answer the formulation of the problem that has been determined so that this research is an exploratory descriptive. As the population in this study were all students of SDN Guluk-guluk I Kec. Guluk-guluk in the academic year 2010/2011 as many as 335 students. For the purposes of analysis in this study, primary data are needed as the main data and secondary data as complementary data. The method of obtaining primary data as the main data will be used by using a questionnaire technique or by using a questionnaire. To obtain more complete data information in this study, observation and documentation techniques were also used. So that the data collection techniques in this study used questionnaires, documentation and observation. Reliable services, responsive services, convincing services, empathic services, and service provider facilities have a significant effect on Student Satisfaction at SDN Guluk-guluk I Kec. Guluk - guluk , this is indicated by using the F test shows the value of F count of 143.161 (significance f = 0.000) so Fcount> Ftable (143.161> 3.095) or Sig F <5% (0.000 <0.05) means the magnitude of the influence of quality variables service (X1) to student satisfaction (Y) of 90.00%. Partially Service Quality Management has a significant positive effect on Student Satisfaction at SDN Guluk-guluk I Kec. Gulul-guluk, this is indicated by the t count value of 5.221 with a significance of 0.000, because tcount> ttable (5.221> 1.986 ) or sig t <5% (0.000 <5%) and the value of the partial regression coefficient (standardized beta coefficients) is 0.595 then partially the service quality variable (X2) has a significant positive effect on the student satisfaction variable at SDN Guluk-guluk I Kec. Roll up (Y) Reliable service, responsive service, convincing service, empathic service, and service provision of facilities together have an effect on student satisfaction. Service quality management which more dominantly affects student satisfaction than other variables, this can be seen from the value of the regression coefficient (standardized coefficients beta) which is the largest compared to the coefficient value on the facility provision variable of 0.595 which shows the regression value of the service quality variable (X1) of 0.296.